Effect of eccentric strength training and static stretch on hamstring flexibility among futsal players - Wan Firdaus Wan Chik (Tanjong Malim, 2019)
Effect of eccentric strength training and static stretch on hamstring flexibility among futsal players by Wan Firdaus Wan Chik